2021
DOI: 10.7554/elife.72104
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous clocks that regulate organelle biogenesis, cytoskeletal organization, and intracellular dynamics

Abstract: How do cells perceive time? Do cells use temporal information to regulate the production/degradation of their enzymes, membranes, and organelles? Does controlling biological time influence cytoskeletal organization and cellular architecture in ways that confer evolutionary and physiological advantages? Potential answers to these fundamental questions of cell biology have historically revolved around the discussion of ‘master’ temporal programs, such as the principal cyclin-dependent kinase/cyclin cell division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 173 publications
1
22
0
Order By: Relevance
“…Furthermore, chromosome endoreduplication [ 76 ] and basal body (centriole) amplification [ 77 ] are characteristics of certain terminally differentiated (non-dividing) cells. These observations support the ‘clock-shop' hypothesis [ 71 , 72 , 78 ], although there are opposing opinions [ 73 , 79 , 80 ]. In the future, we may expect continued debate on the possible roles of ‘autonomous clocks' in cell cycle progression.…”
Section: Other Recent Developments In Time-keepingsupporting
confidence: 60%
“…Furthermore, chromosome endoreduplication [ 76 ] and basal body (centriole) amplification [ 77 ] are characteristics of certain terminally differentiated (non-dividing) cells. These observations support the ‘clock-shop' hypothesis [ 71 , 72 , 78 ], although there are opposing opinions [ 73 , 79 , 80 ]. In the future, we may expect continued debate on the possible roles of ‘autonomous clocks' in cell cycle progression.…”
Section: Other Recent Developments In Time-keepingsupporting
confidence: 60%
“…While considerable progress has been made toward understanding the biophysical properties and the biological functions of biomolecular condensates and LLPS ( 38 ), it remains elusive whether LLPS dynamics are under the control of “autonomous clocks” ( 39 ). Our study hereby demonstrates the existence of an evolutionarily conserved XBP1s-SON axis that integrates the 12-hour oscillator with nuclear speckle LLPS to spatiotemporally program proteostasis ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the autonomous cycles of centriole duplications, which occur at a natural period of ~17min, where nuclear cycles appear to help speed up centriole biogenesis in wild-type conditions (11). Together, these findings provide a striking new evidence for the emerging concept of "autonomous clocks" in which the Cdk-cyclin oscillator is postulated to couple otherwise autonomous biological cycles to run at the pace of nuclear cycles (7,11,40,41).…”
Section: Main Textmentioning
confidence: 86%
“…Prevailing models of mitotic progression have long promoted the idea that the rising levels of Cyclin-dependent kinase 1 (Cdk1) activity ( 3, 4 ) and/or affinity for substrates ( 5, 6 ) triggers cell cycle events. Recent work, however, has clearly demonstrated that some events can happen independently of Cdk1 activity ( 7, 8 ). For instance, centrioles can duplicate autonomously when the cell cycle is halted, both by perturbations in dividing cells ( 911 ) and naturally in non-dividing cells ( 12 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation